2020
DOI: 10.4103/ccd.ccd_9_19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical disinfection on surface detail reproduction and dimensional stability of a new vinyl polyether silicone elastomeric impression material

Abstract: Background: Surface detail reproduction (SDR) and dimensional stability of elastomeric impression material play a crucial role in fixed prosthodontics. Aim and Objectives: The aim of this study was to compare the effect of chemical disinfection on SDR and dimensional stability of polyvinyl siloxane (PVS) and polyether (PE) with a new vinyl polyether silicone (VPES) elastomeric impression material. Materials and Methods: A stainless steel mold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
2
0
3
Order By: Relevance
“…These findings were in correlation with the results of the present study as the dimensional changes in the test samples were within clinically acceptable range both for 10 mins and 30 mins. A thirty-minute glutaraldehyde disinfection time was recorded in only one investigation, whereas a three-minute Cavex disinfection time was observed in another [22,25]. The immersion technique with a ten-minute disinfection interval was employed in most of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were in correlation with the results of the present study as the dimensional changes in the test samples were within clinically acceptable range both for 10 mins and 30 mins. A thirty-minute glutaraldehyde disinfection time was recorded in only one investigation, whereas a three-minute Cavex disinfection time was observed in another [22,25]. The immersion technique with a ten-minute disinfection interval was employed in most of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Weżgowiec et al found that the chemical immersion disinfection method had no significant impact on the dimensional stability of the PVS impressions ( Weżgowiec et al, 2022 ). However, Khatri et al reported significant dimensional changes at a 3 % NaOCl concentration using the same duration for immersion disinfection ( Khatri et al, 2020 ). The observed dimensional changes might have been influenced by the 12-hour waiting period after disinfection, which could explain the variation in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha observado microorganismos potencialmente patógenos después de la toma de la impresión como es el caso de: Streptococcus, Staphylococcus, Staphylococcus aurerus, ,Staphylococcus resistente a la meticilina, Escherichia coli, Mycobacerium, tuberculosis, cándida además de virus de hepatitis B, C virus de la inmunodeficiencia humana, virus de herpes simple (6-8-15-16). La principal desventaja de la desinfección son los cambios dimensionales que se pueden presentar al ser expuesto a este proceso (3)(4)(5)(6)(7)(8). La elección de desinfectantes depende de la toxicidad, el daño que puede generar a la superficie, la estabilidad y la rapidez de eliminación microorganismo (17).…”
Section: Desinfectantes Utilizados En Odontologíaunclassified
“…Presenta una concentración del 2 al 2,15% (7), además su acción consiste en fijarse a la membrana y bloquear la liberación de componentes celulares lo que destruye a los microorganismos (2).…”
Section: Glutaraldehídounclassified
See 1 more Smart Citation